2021
DOI: 10.3390/agronomy11030417
|View full text |Cite
|
Sign up to set email alerts
|

HPLC-DAD Polyphenolic Profiling and Antioxidant Activities of Sorghum bicolor during Germination

Abstract: The purpose of this study was to assess the suitability of the Romanian Albanus hybrid of Sorghum bicolor as a potential functional food ingredient. Ultrasound-assisted extraction in different solvents, together with spectrophotometric and chromatographic methods, was used to monitor the variation in total phenolic and flavonoid content and the antioxidant activity of raw sorghum grains before and during short germination periods (24, 36 and 48 h). The High-Performance Liquid Chromatography with Diode-Array De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
(35 reference statements)
1
10
0
Order By: Relevance
“…It presented a UV λ max at 325 nm and had a comparable spectrum to the one from chlorogenic acid reported in literature ( Robbins, 2003 ). This compound was also found in sorghum in previous studies, with a similar retention behavior ( Ghinea et al, 2021 ). Moreover, a study on millet reported its presence only in a free form ( Chandrasekara and Shahidi, 2011 ).…”
Section: Discussionsupporting
confidence: 85%
“…It presented a UV λ max at 325 nm and had a comparable spectrum to the one from chlorogenic acid reported in literature ( Robbins, 2003 ). This compound was also found in sorghum in previous studies, with a similar retention behavior ( Ghinea et al, 2021 ). Moreover, a study on millet reported its presence only in a free form ( Chandrasekara and Shahidi, 2011 ).…”
Section: Discussionsupporting
confidence: 85%
“…For the calibration curves, concentrations between 10 and 400 µg/mL were used. The total polyphenols were analyzed at 300 nm detection [97][98][99].…”
Section: General Procedures For the Synthesis Of The Gold Nanoparticlesmentioning
confidence: 99%
“…After 30 min of standing at room temperature, the samples were placed in a Tecan Pro 200 multiwell plate reader (Tecan, Männedorf, Switzerland) and their absorbance was recorded at 760 nm. As the standard references, gallic acid (0.97-500 µg/mL) and tannic acid (0.97-500 µg/mL) were used, and the results were expressed as equivalents of gallic acid (mg GAEq/g) and tannic acid (mg TAEq/g) per 1 g of sample [97][98][99].…”
Section: General Procedures For the Synthesis Of The Gold Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, non-enzymatic antioxidants, such as flavonoids and phenolic acids, are significantly involved, too. Flavonoids are known as good antioxidants that are able, due to the fact of their polyphenolic structure, to scavenge free radicals and chelate divalent cations [8,9]. Rich sources of these compounds are fruit, vegetables, nuts, seeds, and beverages (fruit wine, grape wine, as well as tea) [10][11][12].…”
Section: Introductionmentioning
confidence: 99%